Suggested Research Trends in the Area of Micro-EDM—Study of Some Parameters Affecting Micro-EDM - Atanas Ivanov; Abhishek Lahiri; Venelin Baldzhiev; Anna Trych-Wildner (Micromachines, 2021)
This paper provides an overall view of the current research in micro-electrical discharge machining (micro-EDM or µEDM) and looks into the present understanding of the material removing mechanism and the common approach for electrode material selection and its limitations. Based on experimental data, the authors present an analysis of different materials’ properties which have an influence on the electrodes’ wear ratio and energy distribution during the spark. The experiments performed in micro-EDM conditions reveal that properties such as electron work function and electrical resistivity strongly correlate with the discharge energy ratio. The electrode wear ratio, on the other hand, is strongly influenced by the atomic bonding energy and was found to be related to the tensile modulus. The proposed correlation functions characterized the data with a high determination coefficient exceeding 99%.